Side effects of COVID-19 vaccines among Iranian healthcare workers: a retrospective cohort study - Hassan Roudgari; Koorosh Etemad; Manoochehr Karami; Farideh Mostafavi; Sahar Sotoodeh Ghorbani; Kosar Farhadi Babadi; Elham Rahimi; Niloufar Taherpour; Seyed Mahmood Fattahi Masoom; Masoud Habibi; Hossein Kermanpour; Reza Laripour; et al. (Journal of Infection in Developing Countries)
Introduction: This study assessed the incidence and severity of side effects associated with coronavirus disease 2019 (COVID-19) vaccination among healthcare workers registered with the Medical Council of the Islamic Republic of Iran.